ANÁLISE DO DESEMPENHO DOS ATLETAS NAS PROVAS COMBINADAS NO PERÍODO DE 2000 A 2012 - João Paulo Kaiut; Alberto Inácio da Silva; Aguinaldo José do Nascimento (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
The aim of this study was analyze the results obtained by decathlon and heptathlon athletes, in the youth category races, during the Brazilian championship between of 2000-2012. This study is classified as a descriptive and retrospective. As database we used the information available on the Brazilian Athletics Confederation, South American Athletics Confederation and the International Association of Federations Athletics websites on the Youth category combined events, which includes female athletes aged 13-17 years old. Data were subjected to analysis of variance (ANOVA) with two-way, followed by the Tukey test for comparisons between the average performances. To assess the decrease in performance over the years was used for monitoring the slope coefficient of the regression analysis. The analyzing the data shows that of 78 medals (gold, silver and bronze) distributed in 13-year period among the genders (Male and Female), athletes 17 years old are the most awards, followed by athletes of 16 years. Despite attempts to popularization of sport throughout Brazil, it is observed that there are few states that can stand in athletics. The São Paulo state was the highest winner (43.59% of medals distributed) followed by Rio de Janeiro state (20.51% of the medals distributed).